A Legal Analysis of Marine Tourism Development and Investment within the Framework of the Special Economic Zone in Sekotong Subdistrict, West Lombok Regency - Ariel Alexander; Boy Gabriel Yohanes Simarmata; Dyo Ganda Siadari; Udin Silalahi (Eduvest - Journal of Universal Studies, 2026)
Marine tourism development in Sekotong District, West Lombok Regency, has grown rapidly as part of an investment strategy within a special economic zone framework. However, this expansion raises legal issues related to coastal governance, environmental protection, and social justice for local communities. This research aims to conduct a normative juridical analysis of marine tourism development and investment to evaluate the consistency, synchronization, and harmonization of legal norms governing coastal and investment regulations. The research applies a normative juridical approach focusing on statutory analysis and secondary legal materials as the primary sources of examination. The findings indicate that Indonesia possesses a relatively comprehensive legal framework, yet regulatory disharmony, institutional coordination weaknesses, and the risk of unequal economic benefit distribution remain potential challenges. Without consistent legal governance, these conditions may trigger social conflict and ecological pressure. Therefore, strengthening regulatory harmonization and sustainability-oriented legal approaches is essential to ensure fair and sustainable marine tourism development.